Pendampingan Digitalisasi UMKM Binaan Di Kelurahan Sendangtirto, Berbah, Sleman Diy - Indani, Farinza Tiara; Wahyuningsih, Adityas; Andriani, Juwita; Arifah, Amalina Nur; Sulistyowati, Andita (STMIK Royal, 2024)
MSMEs in Indonesia are a potential basis for a strong national economy because of their large number, especially micro businesses, and their labor absorption capacity is very large. Sendangtirto Village, which is part of the Berbah District Area, Sleman Regency, DIY, also has quite large MSME potential. By knowing and mapping the potential of MSMEs in Sendangtirto and assisting by providing training outreach and mentoring on the digitalization of Sendangtirto MSMEs, it is hoped that it will advance and be able to develop MSMEs, increasing competitiveness with the integration of digital platforms. This service function aims to apply and disseminate the knowledge and skills possessed by academics to the wider community, as well as contributing directly to improving the quality of life and sustainable development. The results of data analysis from the questionnaire showed a significant increase in participants' understanding after the socialization. The participants' positive response to the benefits and ease of use of digital platform robots for ease in digitalizing MSMEs illustrates the success of this socialization. Keywords: digitalization; socialization;potential of MSMEs